Association between mothers' problematic Internet use and maternal recognition of child abuse. (October 2019) - Sakakihara, Aya; Haga, Chiyori; Kinjo, Aya; Osaki, Yoneatsu
Abstract: Background: There are few studies about mothers' problematic Internet use (PIU). Mothers' PIU may lead to inadequate parenting and child abuse. Objective: This cross-sectional study aimed to clarify the association between mothers' PIU and their recognition of child abuse. Participants and setting: We analyzed data collected of health examinations of children aged 4 months, 1.5 years, and 3 years which were carried out in Matsue City, Shimane Prefecture, Japan between April 2016 and March 2017. The number of the subjects were 1685, 1729, 1674, respectively. Methods: We used logistic regression analysis to clarify the association between mothers' PIU (Young's Diagnostic Questionnaire for Internet Addiction score: ≥5) and their recognition of child abuse (selecting < True of me > for < I sometimes think that I am abusing my child > on a questionnaire survey), which was adjusted for covariates such as maternal age, number of children, daytime caretaker, social support, postpartum depression, and current smoking status of the parents. Results: Based on the multivariate logistic regression analysis, the mothers' PIU was significantly correlated with their recognition of child abuse for children aged 4 months, 1.5 years, or 3 years [odds ratio (OR): 13.30, 95% confidence interval (CI): 1.26–139.98, OR: 7.02, 95% CI: 1.28–38.55, and OR: 28.06, 2.48–317.93, respectively]. Conclusion: This study revealed the possibility that mothers with PIU recognize child abuse more than mothers without PIU. However, further studies should be conducted to increase reliability and validity.